(untitled) - David, Andrej (Doprava a spoje, 2009)
Because of increase of containers in the 1980s shipyards started building a new generation of container ships (also called Post Panamax). Container cranes, which transfer containers among container ships and the berth of seaports had to increase their output, outreach and lifting capacity because of 16 rows of containers on the deck and bigger transport capacity.